Potential of rubberwood (Hevea brasiliensis) for structural use after the period of latex extraction: a case study in Brazil - de Jesus Eufrade Junior, Humberto [UNESP]; Ohto, Jéssica Monari [UNESP]; da Silva, Lucas Luís [UNESP]; Lara Palma, Hernando Alfonso [UNESP]; Ballarin, Adriano Wagner [UNESP] (Springer Nature, 2015)
In Brazil, after the cycle of latex extraction, rubber plantations are reformulated and the wood of these plantings are traditionally used as a cheap source for energy purposes. Rubberwood has other uses based on the consolidated experience in Asian countries. The aim of this article was to evaluate the technological potential of the wood of two main commercial clones of Hevea brasiliensis in Brazil, RRIM600 and GT1, after the period of latex extraction. To accomplish this objective, some physical and mechanical properties of wood were analyzed. The clones had a basic density greater than 0.540 g cm−3, low volumetric shrinkage (<10 %), and medium to high strength in compression parallel to grain (>40 MPa). According to the results obtained, rubberwood has applications in small and secondary structures, lightweight construction, and furniture industry and it can be an alternative in the Brazilian market to reduce the timber demand from native forest species.
Keywords: Basic density; Hevea brasiliensis; Mechanical properties; Wood technological potential